Novel rice-based cropping systems with legumes and vegetables in Cote d'Ivoire - CGIAR Research Program on Rice (2021)
Off-season crops production in rotation to rainfed rice under different irrigation scheduling was assessed in inland valleys of Cote d’Ivoire using a participatory approach. The highest net income was obtained with tomato – rice system with irrigation supply based on the readily available moisture (5.275 mm) supplied every 3 days.